2023
DOI: 10.5851/kosfa.2022.e68
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Lactobacillus reuteri MG5346 on Receptor Activator of Nuclear Factor-Kappa B Ligand (RANKL)-Induced Osteoclastogenesis and Ligature-Induced Experimental Periodontitis Rats

Abstract: Effects of culture supernatants of Lactobacillus reuteri MG5346 (CS-5346) on receptor activator of nuclear factor-kappa B ligand (RANKL)-induced osteoclastogenesis were examined. CS-MG5346 treatment up to 400 μg/mL significantly reduced tartrate-resistant acidphosphatase (TRAP) activity, the phenotype biomarker of osteoclast, without affecting cell viability. CS-MG5346 inhibited the expression of osteoclast specific transcriptional factors (cfos and nuclear factor-activated T cells c1) and their target genes (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Periodontitis is a typical chronic inflammatory disease that is associated with not only gingival inflammation but also alveolar bone loss. The occurrence of bone resorption indicates that homeostasis in periodontal tissue is absent under inflammatory conditions [ 38 ].The treatment effect of curcumin in periodontal disease includes anti-inflammation and relieves alveolar bone resorption. Therefore, we have further detected ferroptosis related markers in alveolar bone tissues.…”
Section: Resultsmentioning
confidence: 99%
“…Periodontitis is a typical chronic inflammatory disease that is associated with not only gingival inflammation but also alveolar bone loss. The occurrence of bone resorption indicates that homeostasis in periodontal tissue is absent under inflammatory conditions [ 38 ].The treatment effect of curcumin in periodontal disease includes anti-inflammation and relieves alveolar bone resorption. Therefore, we have further detected ferroptosis related markers in alveolar bone tissues.…”
Section: Resultsmentioning
confidence: 99%
“…CFSs from the postbiotics Lactobacillus salivarius and Lactobacillus reuteri have considerable potential as functional oral health ingredients to inhibit alveolar bone loss associated with periodontitis [ 25 , 38 ]. Meanwhile, the W. cibaria CMU (oraCMU) and CMS1 (oraCMS1) strains have been commercialized as oral probiotics, and there has been ongoing research on their beneficial effects on oral health [ 18 , 19 , 20 , 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that B. lactis HN019 could reduce the expression of RANKL, but had no effect on the level of OPG [51]. In addition, L. reuteri MG5346 can signi cantly reverse the ratio of OPG to RANKL in periodontitis rats' gingival tissue [52]. Dental plaque bio lms have the capability to upregulate RANKL while downregulating OPG expression, resulting in a reduction of the OPG/RANKL ratio [53][54][55][56].…”
Section: Disscussionmentioning
confidence: 99%